Posmodern Thinking and Relativism Theory in the Field of Pedagogy - Gojkov, Grozdanka (Revija za elementarno izobraževanje, 2019)
According to theoretical analysis, the text considers the influence of an understanding of postmodern thinking on pluralistic perspectives in education, pluralisation of the concepts of upbringing and education, critique of concepts like causality in gnoseological and epistemological assumptions – determinism, objectivity, rationalization and its consequences in the fields of, e.g., morality. It turns out that the traditional humanistic concepts of education and forming of personality, on the one hand, and learning and knowledge, on the other, demand reconsideration from a perspective involving postmodern scepticism about the idealistic and rigid preconceptions of modern thought. This raises the further question of the efficacy of modern pedagogy in the sense of its consistency with its scientific aims, i.e. its function.